Aplikasi Pengenalan Alat Transportasi Berbasis Android Untuk Mengoptimalkan Stimulasi Aspek Kognitif Anak Usia 5-6 Tahun - Anjani, Ratna; Nabila, Siti Winda Mariam; Nuraeni, Cucu (Institut Agama Hindu Negeri Gde Pudja Mataram, 2024)
The application of the introduction of android-based transportation tools to optimize the cognitive aspects of children aged 5-6 years created by three students of the Early Childhood Education Teacher Education study program at the University of Education Indonesia. This research uses the R&D (Research and Development) method through six research flows. This application is suitable for use by children who have been validated by media and material experts. This application has been tested at PAUD Az-zahra Pandeglang City. The results of the trial are in accordance with the purpose of making the application, which is to increase accuracy, develop children's critical thinking skills and problem-solving abilities, distinguish between different types of goods, and develop their emotional intelligence. In addition, this application is user-friendly, can increase children's interest and motivation to learn, encourage critical thinking and problem solving skills in children and is relevant to be used as a teaching aid at PAUD Az-zahra Pandeglang City.